y-(5-2y)=7(y-1)-2

Simple and best practice solution for y-(5-2y)=7(y-1)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y-(5-2y)=7(y-1)-2 equation:


Simplifying
y + -1(5 + -2y) = 7(y + -1) + -2
y + (5 * -1 + -2y * -1) = 7(y + -1) + -2
y + (-5 + 2y) = 7(y + -1) + -2

Reorder the terms:
-5 + y + 2y = 7(y + -1) + -2

Combine like terms: y + 2y = 3y
-5 + 3y = 7(y + -1) + -2

Reorder the terms:
-5 + 3y = 7(-1 + y) + -2
-5 + 3y = (-1 * 7 + y * 7) + -2
-5 + 3y = (-7 + 7y) + -2

Reorder the terms:
-5 + 3y = -7 + -2 + 7y

Combine like terms: -7 + -2 = -9
-5 + 3y = -9 + 7y

Solving
-5 + 3y = -9 + 7y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-7y' to each side of the equation.
-5 + 3y + -7y = -9 + 7y + -7y

Combine like terms: 3y + -7y = -4y
-5 + -4y = -9 + 7y + -7y

Combine like terms: 7y + -7y = 0
-5 + -4y = -9 + 0
-5 + -4y = -9

Add '5' to each side of the equation.
-5 + 5 + -4y = -9 + 5

Combine like terms: -5 + 5 = 0
0 + -4y = -9 + 5
-4y = -9 + 5

Combine like terms: -9 + 5 = -4
-4y = -4

Divide each side by '-4'.
y = 1

Simplifying
y = 1

See similar equations:

| 5+1=3 | | 3x+7=3+5x-8 | | (X+2)=49 | | (a+30)=(a-18) | | (a+16)=(a-18) | | (5x+14)=(86-4x) | | 4x-2x-18=x+6 | | (a+16)=(a+30) | | r/4-7=-3 | | x-39=17 | | (9+7x)=(75+x) | | zy= | | 2y-42-3y=5y | | 21y-14x=71 | | 0.50x+0.25(50)=47.5 | | (5x-5)=(15x-115) | | h[x]=6-3x | | 8x/3=11x+9/4 | | y=sx+b | | 64-7x=11x+16 | | 4x-6x=14 | | 3x=(11x-80) | | 0.285x^2-x+2=0 | | 9x=6+6x | | -3y-6=48 | | 2x-9=19-5x | | 10y/15-28,5/15=6y/10 | | 3/4(2x+8)=2(4-4x)+17 | | 4(3-y)+8=12(3-y) | | 1/2+3/4p=1/4 | | x=1/5(90-x) | | 1/4x^2+3/4x=1 |

Equations solver categories